Comparison of transabdominal ultrasound and electromagnetic transponders for prostate localization - Foster, Ryan D. (J Appl Clin Med Phys, 2010)
The aim of this study is to compare two methodologies of prostate localization in a large cohort of patients. Daily prostate localization using B‐mode ultrasound has been performed at the Nebraska Medical Center since 2000. More recently, a technology using electromagnetic transponders implanted within the prostate was introduced into our clinic (Calypso). With each technology, patients were localized initially using skin marks. Localization error distributions were determined from offsets between the initial setup positions and those determined by ultrasound or Calypso. Ultrasound localization data was summarized from 16,619 imaging sessions spanning seven years. Calypso localization data consists of 1524 fractions in 41 prostate patients treated in the course of a clinical trial at five institutions and 640 localizations from the first 16 patients treated with our clinical system. Ultrasound and Calypso patients treated between March and September 2007 at the Nebraska Medical Center were analyzed and compared, allowing a single institutional comparison of the two technologies. In this group of patients, the isocenter determined by ultrasound‐based localization is on average 5.3 mm posterior to that determined by Calypso, while the systematic and random errors and PTV margins calculated from the ultrasound localizations were 3–4 times smaller than those calculated from the Calypso localizations. Our study finds that there are systematic differences between Calypso and ultrasound for prostate localization. PACS number: 87.63.dh